The Development Path of Disciplinary Characteristics of Specialized Universities in China - Ma Guotao; Dai Jiajia (Randwick International of Education and Linguistics Science Journal, 2023)
In the development of universities, disciplines carry many functions, such as personnel training, scientific research and social services. All kinds of organizations and activities of universities are centered on disciplines and developed around the development of disciplines. As an industrial university, the discipline characteristics are accumulated in the long-term history of running a school, and also created in the service of economic and social development, which is different from other universities. Based on the analysis of the influencing factors of discipline development in industrial universities, this paper holds that industrial universities should persist in optimizing discipline layout, concise discipline direction, take the road of characteristic development and win by comparison, which is also the only way to build a "double-first-class" world-class university.